THE EFFECT OF CORPORATE GOVERNANCE ON EARNINGS MANAGEMENT IN NIGERIA’S FINANCIAL INSTITUTIONS: MODERATING ROLE OF CEO COMPETENCY (Malaysian Management Journal, 2023)
The purpose of this paper is to examine the moderating effect of CEO competency on the relationship between corporate governance (CG) and earnings management (EM) of Nigerian financial firms. The sample covered 37 financial firms listed in the Nigeria Stock Exchange (NSE) from 2010 to 2019. This study adopted a panel regression estimator to analyse the testable hypotheses. It was found that CEO competency only moderated the relationship between audit committee and EM but not on the other CG variables. This finding implied that CEO competency was important when accounting oversight was in balance with EM. While the agency hypothesis on CG was supported, the study upheld the idea that CEO competency undermined EM. As a result, the study advocates for broader CEO oversight and resource measures, including CEO remuneration and CEO social capital, to lessen the impact of CG in the EM of financial institutions. The effect of the Covid-19 crisis on the link between CG and EM should be the subject of future studies. Future research should examine how the Covid-19 issue affects the CG mechanism’s ability to reduce EM and determine whether the effect is positive or negative.